2018
DOI: 10.1016/j.maturitas.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activity during walking and balance tasks in older adults and in people with Parkinson’s disease: A structured review

Abstract: An emerging body of literature has examined cortical activity during walking and balance tasks in older adults and in people with Parkinson's disease, specifically using functional near infrared spectroscopy (fNIRS) or electroencephalography (EEG). This review provides an overview of this developing area, and examines the disease-specific mechanisms underlying walking or balance deficits. Medline, PubMed, PsychInfo and Scopus databases were searched. Articles that described cortical activity during walking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
119
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 88 publications
9
119
0
4
Order By: Relevance
“…However, these findings are still preliminary and it is not yet clear if there is a specific pattern according to age or cognitive status, nor about how these differences should be interpreted. Recently published reviews have assessed the results of studies on fNIRS during cognitive tasks (Herold et al, 2018) or dual tasks (Gramigna et al, 2017;Herold et al, 2017;Leone et al, 2017;Vitorio et al, 2017;Stuart et al, 2018;Kahya et al, 2019) and some of them have chosen to focus on specific clinical profiles (Gramigna et al, 2017;Vitorio et al, 2017) or on methodological aspects such as fNIRS signal processing (Herold et al, 2017(Herold et al, , 2018Vitorio et al, 2017). To the best of our knowledge, our review is the first to focus specifically on older adults regardless of their clinical profile and to assess, from a clinical point of view, studies using only cognitive or motor tasks, as well as DTs.…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings are still preliminary and it is not yet clear if there is a specific pattern according to age or cognitive status, nor about how these differences should be interpreted. Recently published reviews have assessed the results of studies on fNIRS during cognitive tasks (Herold et al, 2018) or dual tasks (Gramigna et al, 2017;Herold et al, 2017;Leone et al, 2017;Vitorio et al, 2017;Stuart et al, 2018;Kahya et al, 2019) and some of them have chosen to focus on specific clinical profiles (Gramigna et al, 2017;Vitorio et al, 2017) or on methodological aspects such as fNIRS signal processing (Herold et al, 2017(Herold et al, , 2018Vitorio et al, 2017). To the best of our knowledge, our review is the first to focus specifically on older adults regardless of their clinical profile and to assess, from a clinical point of view, studies using only cognitive or motor tasks, as well as DTs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous fNIRS studies have been limited to examination of only PFC activity with differences in the activation across other cortical areas under dual-task walking only investigated in young adults (20,21,40), therefore age-related regional differences are unknown (41). Imaging studies have demonstrated that gait is complex and involves multiple cortical regions (24,42).…”
Section: Introductionmentioning
confidence: 99%
“…The neural mechanisms associated with age-and disease-related gait changes have been investigated using neuroimaging techniques, such as functional magnetic resonance imaging (fMRI), near-infrared spectroscopy (NIRS) and electroencephalography (EEG). Studies using these imaging techniques have shown that gait-related brain activity differs in older adults and people with PD (Maillet et al 2012, Bohnen & Jahn 2013, Herman et al 2013, Hamacher et al 2015, Stuart et al 2018, Wilson et al 2018. For example, older adults exhibit greater activity in various cortical regions including motor, somatosensory, visual and frontal cortices than young individuals during gait imagery as revealed by fMRI (Wai et al 2012, Zwergal et al 2012, Allali et al 2014.…”
Section: Introductionmentioning
confidence: 99%